(untitled) (Fiep Bulletin - online, 2015)
The prevalence of diabetes is increasing worldwide, setting up currently as a result epidemic, largely of aging. However, physical inactivity, poor diet and increasing obesity are also responsible for the global expansion of diabetes. The ergogenic nutritional supplements are those that can promote increased physical performance beyond the physiological capacity and have a thermogenic action in the body. However, the biological activity and scientific validation of these supplements still require studies for clinical evidence as to its thermogenic benefits, thus casting doubt on the effectiveness of these substances. The objective of this study was to evaluate the effect of supplementation with dextrose on blood glucose levels in diabetic animals 2. For this type was used 38 male Wistar rats, 14 and 24 normoglycemic diabetic animals were subjected to metabolic cage in order to verify the consumption of food and water, urine volume and glucosuria, after that were treated with dextrose, and subjected to biochemical tests. Our results indicate that supplementation with dextrose, one ergogenic substance often used in physical activities and exercises no induces hyperglycemia in diabetic animals or abnormal liver function in these animals